2019
DOI: 10.1371/journal.pone.0225444
|View full text |Cite
|
Sign up to set email alerts
|

Does craniofacial morphology affect third molars impaction? Results from a population-based study in northeastern Germany

Abstract: ObjectivesIt is still not clear why impaction of third molars occurs. Craniofacial morphology and facial parameters have been discussed to be strong predictors for third molar impaction. Thus, this study aimed to investigate the effect of craniofacial morphology on erupted or impacted third molars in a German population sample.Materials and methodsErupted and impacted third molars in 2,484 participants from the Study of Health in Pomerania were assessed by whole-body magnetic resonance imaging. Markers of faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Another study reported that impacted mandibular 3rd molars were associated with decreased faciocranial height and increased cranial width. 8,36 This study has certain limitations. As mentioned earlier, if there had been a sufficient number of samples in the subgroups formed in Groups 1 and 2, we planned to conduct analyses in two main and four subgroups in total.…”
Section: Discussionmentioning
confidence: 94%
“…Another study reported that impacted mandibular 3rd molars were associated with decreased faciocranial height and increased cranial width. 8,36 This study has certain limitations. As mentioned earlier, if there had been a sufficient number of samples in the subgroups formed in Groups 1 and 2, we planned to conduct analyses in two main and four subgroups in total.…”
Section: Discussionmentioning
confidence: 94%
“…Kindler et al [ 28 ] studied the effect of craniofacial morphology on erupted or impacted third molars using MRI. They found that an increased maximal cranial width has a higher risk for impaction of third molars in the mandible and in the maxilla, and that individuals with a lower total anterior facial height and lower facial index also are at an increased risk for third molars impaction in the mandible.…”
Section: Resultsmentioning
confidence: 99%
“…However, this study was recently discredited due to the restricted sample size [ 8 ]. Impaction of the mandibular third molar seems to be associated with increased cranial width and decreased cranial facial height [ 34 ].…”
Section: Discussionmentioning
confidence: 99%